Agricultural Precision: Transformation and Sustainability - Ni Luh Putu Sulis Dewi Damayanti; Anak Agung Sagung Manik Chindrawati; Yohanes Parlindungan Situmeang (Agriwar Journal, 2023)
Agriculture, a crucial provider of food and raw materials, is evolving in response to technological advancements and population growth. Precision agriculture (PA), coupled with biochar utilization, has emerged to address global challenges such as resource scarcity, climate change, and rising food demands. PA employs IoT sensors for plant monitoring, enhancing efficiency and sustainability. The growing role of technology has sparked concerns about the environmental impact of modern agriculture, necessitating a balance between productivity and environmental preservation. Biochar, produced through biomass pyrolysis, offers soil benefits like improved structure and water retention while reducing CO2 emissions and enhancing nutrient availability. Despite challenges like environmental variation and cost, opportunities lie in advanced research, partnerships, policies, waste management, and carbon footprint reduction. This literature study highlights the synergy between precision agriculture and biochar, showcasing potential for transformative and sustainable agricultural practices that address global food needs while safeguarding the environment.